The big rock - Hiscock, Bruce (New York : Atheneum, 1988)
Traces the origins of a granite rock located near the Adirondack Mountains and describes how it reveals information about the history of the earth.
Keywords: Rocks -- Juvenile literature; Geology -- Juvenile literature; Rocks; Geology